Contextualising ethics in the practice of translator education: the case of the indigenous value system of the Basotho - Marais, Kobus (University of the Free State, 2012)
This article develops the suggestions made in recent publications on translation studies concerning the role of the translator as an agent. The article discusses agency as a central theme in translation, and points out that it is not a value unto itself, but that it must be conceptualised within a value system. This value system, it is contended, is inculcated during the years of study at tertiary institutions. This suggests that the value system must be incorporated into the curriculum, the choice of which is left in the hands of the lecturer. Following the lead of Tymoczko, who argued for the internationalisation of translation studies, the indigenous Basotho value system and the concept of ubuntu, with its concomitant values, are explored as values that may be of interest to translation studies. If the study of translation is to be contextualised, so does ethics in translator education. The article reconsiders the implications of critical studies for ethics, arguing that it creates an impasse for human ethical action. As a value system that nurtures society and individuality, ubuntu may be a valuable alternative.

Hierdie artikel bou voort op die voorstelle wat in onlangse publikasies in vertaalkunde oor die rol van die vertaler as ’n agent aan die hand gedoen is. Die artikel bespreek agentskap as ’n sentrale tema in vertaling en wys daarop dat agentskap nie ’n waarde op sigself is nie, maar dat dit binne ’n waardestelsel gekonseptualiseer moet word. Hierdie waardestelsel word tydens die opvoedingsjare aan hoëronderwysinstellings vasgelê. Die waardestelsel moet dus binne die kurrikulum, waarvan die keuse by die dosent berus, ingebed word. Na aanleiding van Tymoczko se werk, wat ’n saak vir die internasionalisering van die vertaalkunde uitgemaak het, ondersoek die artikel die Basotho se inheemse waardestelsel en die konsep ubuntu, met die gepaardgaande waardes, wat vir die vertaalkunde van belang mag wees. As die bestudering van vertaling gekontekstualiseer moet word, geld dieselfde vir die etiek in vertaleronderrig. Die artikel herbesin oor die implikasies wat die kritiese teorie vir die etiek inhou en argumenteer dat dit ’n impasse vir mense se etiese optrede inhou. As ’n alternatief sou ubuntu, as ’n waardestelsel wat sowel die samelewing as individualiteit koester, van waarde kon wees.
Keywords: Basotho; Translation studies; Translators; Ubuntu